If x^2 + y^2 +1/2 = x + y, find x^y+y^x


If |x|=3x+1, find (64x^2+48x+9)^2018

supermanaccz  Sep 3, 2018

If \(x^2 + y^2 +\frac12 = x + y\), find \(x^y+y^x\).


\(x^2 + y^2 +\frac12 = x + y\) Original, unsimplified equation
\( x^2-x+\frac14=-y^2+y-\frac14\) Moving terms to either side, \(\frac12\)split into \(\frac14's\)
\((x-\frac12)^2=-(y-\frac12)^2\) Rewrote the expressions as squares
\((x-\frac12)^2+(y-\frac12)^2=0\) Added \((y-\frac12)^2\) to both sides
\(x-\frac12=0\ \&\ y-\frac12=0\) Since \(n^2\ge0\), each expression is equal to 0
\(x=\frac12, y=\frac12\) Solved!


Now plugging our values into the expression: 


\(x^y+y^x\Rightarrow \frac12^\frac12+\frac12^\frac12\\ =\sqrt{\frac12}+\sqrt{\frac12}\\ =\frac{1}{\sqrt2}+\frac{1}{\sqrt2}\\ =\frac{\sqrt2}{2}+\frac{\sqrt2}{2}=\boxed{\sqrt2}\)

GYanggg  Sep 3, 2018

If \(|x|=3x+1\), find \((64x^2+48x+9)^{2018}\).


Rewriting expression:


\((64x^2+48x+9)^{2018},\\ =[(8x+3)^2]^{2018},\\ =(8x+3)^{4036}.\)


Solving for \(x\):


\(|x|=3x+1\\ x^2=(3x+1)^2\\ x^2=9x^2+6x+1\\ 8x^2+6x+1=0\\ (2x+1)(4x+1)=0\\ x_1=-0.5, x_2 = -0.25\)


After plugging our values into the equation to check if they work, we will see that only \(-0.25 \) satisfies the equation. 



GYanggg  Sep 3, 2018

7 Online Users


New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.